Manual Dan Komputerisasi: Manakah Yang Lebih Efektif Dalam Penerapan Siklus Akuntansi - Miza Armayra; Elsa Suryanovianti; Muhammad Raihan; Nasywa Syahidah; Reynaldi Farid; Heni Mulyani; Rama Wijaya Abdul Rozak (Akuntansi, 2023)
The Industrial Revolution makes technological developments move quickly beyond human control. In its development, technology is able to change various sectors, one of which is the education sector in learning accounting at the SMK level. Through the presence of this technological development, accounting learning can be done in two ways, namely manual application and computerized application. The purpose of this study is to analyze manual and computerisation: which is more effective in the application of the accounting cycle. This research uses test and questionnaire methods to obtain data and uses literature studies from relevant previous research. In this study, the variables studied were the application of the Manual accounting cycle and the Computer-based accounting cycle variables. The subject of analysis that was compared was all students of class X AKL 4 who attended SMKN 1 Bandung City. The results of this study are that the application of the accounting cycle manually is still used because the basic concepts of the accounting cycle are still learned and more easily understood by students and in terms of costs also does not require large costs. The application of the accounting cycle by computer is more effective and efficient in processing data. The lack of accuracy and untidy workmanship is a weakness in the application of the accounting cycle using the manual method. Having the ability to operate a computer is a weakness in the application of a computerized accounting cycle, therefore the application of a computerized accounting cycle is more complex besides that not everyone is also able to have access to a computer.